Effects of lidocaine and esmolol infusions on hemodynamic changes, analgesic requirement, and recovery in laparoscopic cholecystectomy operations - Dogan,Serpil Dagdelen (2016)
ABSTRACT OBJECTIVE: We compared the effects of lidocaine and esmolol infusions on intraoperative hemodynamic changes, intraoperative and postoperative analgesic requirements, and recovery in laparoscopic cholecystectomy surgery. METHODS: The first group (n = 30) received IV lidocaine infusions at a rate of 1.5 mg/kg/min and the second group (n = 30) received IV esmolol infusions at a rate of 1 mg/kg/min. Hemodynamic changes, intraoperative and postoperative analgesic requirements, and recovery characteristics were evaluated. RESULTS: In the lidocaine group, systolic arterial blood pressures values were lower after the induction of anesthesia and at 20 min following surgical incision (p < 0.05). Awakening time was shorter in the esmolol group (p < 0.001); Ramsay Sedation Scale scores at 10 min after extubation were lower in the esmolol group (p < 0.05). The modified Aldrete scores at all measurement time points during the recovery period were relatively lower in the lidocaine group (p < 0.05). The time to attain a modified Aldrete score of ≥9 points was prolonged in the lidocaine group (p < 0.01). Postoperative resting and dynamic VAS scores were higher in the lidocaine group at 10 and 20 min after extubation (p < 0.05, p < 0.01, respectively). Analgesic supplements were less frequently required in the lidocaine group (p < 0.01). CONCLUSION: In laparoscopic cholecystectomies, lidocaine infusion had superiorities over esmolol infusions regarding the suppression of responses to tracheal extubation and postoperative need for additional analgesic agents in the long run, while esmolol was more advantageous with respect to rapid recovery from anesthesia, attenuation of early postoperative pain, and modified Aldrete recovery (MAR) scores and time to reach MAR score of 9 points.